Compensatory behavior of physical activity in adolescents - a qualitative analysis of the underlying mechanisms and influencing factors - Franziska Beck; Brittany Amel Swelam; Ulrich Dettweiler; Claus Krieger; Anne Kerstin Reimers (BMC, 2024)
Abstract Introduction Compensatory behavior of physical activity (PA) based on the ActivityStat hypothesis in adolescents is scarcely investigated, and existing studies showed inconclusive results. Understanding the compensatory behavior in a holistic way is important as this can help to improve intervention outcomes and thus, increase the PA levels in adolescents. Thus, the aim of the present study is to investigate the occurrence, direction, timeframe, and ratio of habitual activity compensation in adolescents. Furthermore, we want to identify the awareness of compensation and factors that influence compensatory behavior. Methods The present qualitative study used a mixed methods crossover analysis design. Participants (N = 15, 8 boys and 7 girls) were adolescents aged 11-15 years (mean age 13.04 ± 1.28). They provided a habitual weekly schedule with habitual/regular activities and their intensity. Participants then kept an activity diary over one week to capture their actual behavior. After that, data were compared and deviations > ±20% were considered as compensation opportunities. On this basis, deviations were descriptively analyzed for compensatory behavior and were coded as positive and negative compensatory behavior. Further, for each compensation, the ratio of compensation (MET-minutes of the compensating activity/MET-minutes of the activity that was compensated) was calculated. Additionally, interviews were conducted to explore perceptions and influencing factors for (no) compensation. Results Overall, 198 compensation opportunities were identified with deviations greater ± 20%. Of these, 109 opportunities were compensated overall (69 within-day, 40 between-day). Negative compensation took place in 57 opportunities and 52 opportunities were compensated positively. Most of the deviations were overcompensated (compensation/deviation > 100%). About half of the adolescents (N = 8) were not aware about their compensatory behavior, and only one boy was aware of all his compensatory behavior. The most mentioned influence for positive compensation were social support by friends and good weather. As influencing factors for negative compensation, tiredness as well as no need for movement were mentioned predominantly. No negative compensation occurred because adolescents wanted to stick to their routines or participated in hedonistic activities. Discussion Summarizing the findings, the present study delivered new insights into the field of compensatory behavior in adolescents. Nevertheless, compensatory behavior was not consistently observed regarding the occurrence of compensation, direction, timeframe and ratio. However, social support appears to be an important factor to compensate positively or to avoid a negative compensatory behavior. Further, it seems to be helpful to support individuals in their search for hedonistic activities as well as in the establishment of routines.